Conjunctival Inflammatory Nodule in a Patient with Pityriasis Lichenoides et Varioliformis Acuta - Elad Moisseiev; David Varssano (Karger Publishers, 2010)
Aim: To report a case of a patient with pityriasis lichenoides et varioliformis acuta (PLEVA) who developed a conjunctival inflammatory nodule. Case Report: a 13-year-old boy with a diffuse papulovesicular rash diagnosed as PLEVA presented to our clinic complaining of irritation in his right eye. Slitlamp examination revealed a conjunctival inflammatory nodule. His symptoms resolved under topical steroid treatment. Discussion: Pityriasis lichenoides (PL) is a rare condition, diagnosed by a combination of a typical clinical presentation and histopathology. Mucous membrane involvement has been described in severe cases. Ocular involvement in PL has seldom been reported. We suggest that conjunctival inflammatory nodules may be part of the clinical spectrum of this condition and should be looked for and treated in these patients.